The Implications of Early Marriage on Child Development: A Review of Islamic Law - Helmi Jauhar Mubaroq; Sunardi Sunardi; Suratman Suratman (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
Early marriage remains a widespread practice in Indonesia, particularly in Kalipuro District, Banyuwangi, driven by economic factors, culture, and diverse religious interpretations. This study aims to analyze early marriage from the perspective of Islamic law and state law, and evaluate its impact on the physical, psychological, and social development of children. The research employs a normative legal method with conceptual and case approaches, analyzing primary sources including the Quran, hadith, scholarly consensus, fatwas from Islamic institutions, and Indonesian legislation through library research. The findings reveal that Islamic law does not explicitly stipulate a minimum marriageable age but emphasizes physical, emotional, and mental readiness, while state law, through Law No. 16 of 2019, establishes a minimum age of 19 years for both parties. Early marriage in Kalipuro occurs due to economic limitations, promiscuity, and limited knowledge, resulting in financial and emotional neglect of children, reproductive health problems, educational barriers, and suboptimal parenting patterns. The implementation of state law faces challenges in communities that still view early marriage as a solution to social problems, necessitating intensive public education and strict supervision to protect children's rights and the welfare of future generations.